On Environmental Taxation under Uncertainty - Sören Blomquist; Thomas Aronsson (Uppsala University, Department of Economics, 1999)
This paper addresses optimal taxation, when the relationship between consumption and environmental damage is uncertain and treated as a random variable by policy makers. The main purpose is to analyze how additional uncertainty about this relationship affects the optimal unit tax on the consumption good that is causing environmental damage. We find that the optimal response to this tax depends on (i) the attitudes towards risk and (ii) how other policy instruments affect the demand for the good that is causing damage to the environment.
urn:nbn:se:uu:diva-2460
Keywords: D62; D80; H21; Q20; 330; Green taxes; Uncertainty; Optimal taxation; Optimale Besteuerung; Ökosteuer; Risiko; Theorie